High school science teachers’ self-efficacy and teaching practice on socio-scientific issue-based teaching - Ngaoda, Thanawat; Pitiporntapin, Sasithep; Pongsophon, Pongprapan (Kasetsart Journal of Social Sciences, 2026)
Self-efficacy has a tendency for teachers to adopt new instructional methodologies and affects good teaching practices. To enhance science teachers’ self-efficacy and teaching practices using SSI-based teaching in a specific school context, this qualitative study aimed to investigate the following: (1) the level of self-efficacy of in-service science teachers in socio-scientific issue (SSI)-based teaching, (2) the current teaching practices of in-service science teachers in SSI-based teaching, and (3) the relationship between self-efficacy and teaching practices in SSI-based teaching. Fifteen science teachers were selected through purposive sampling at a high school in northeast Thailand. To achieve this, the study used the following instruments: questionnaires to assess the current situation of SSI-based teaching practices and self-efficacy levels and semi-structured interviews to evaluate the SSI-based teaching practices and self-efficacy levels of the study group. The data obtained from the study were analyzed using descriptive statistics and content analysis. The results indicated that the self-efficacy level of the study group in SSI-based teaching was moderate (x̄ = 3.22, SD = 0.99). While five out of the 15 science teachers (33.33%) claimed to use SSI-based teaching in their science classrooms, their teaching practices failed to cover the entire SSI-based teaching framework. The study also found a relationship between self-efficacy and teaching practice in the study group in SSI-based teaching. The study concluded that it is critical to design a professional development program that focuses on enhancing self-efficacy and teaching practices in SSI-based teaching.